Identification and characterization of the neurofibromatosis type 1 protein product. - DeClue, J E (1991)
The neurofibromatosis type 1 (NF1) gene responsible for von Recklinghausen neurofibromatosis is related to regulators of ras proteins, and a portion of NF1 that is homologous to the ras GTPase-activating protein (GAP) encodes a similar GTPase-stimulating activity. We have raised rabbit antisera to a bacterially synthesized 48-kDa peptide corresponding to the GAP-related domain of NF1 (NF1-GRD). These antisera immunoprecipitated the NF1-GRD peptide, and one of them specifically inhibited the GTPase-stimulating activity of NF1-GRD. The sera specifically detected a 280-kDa protein in lysates of mouse NIH 3T3 and human HeLa cells. This protein corresponds to the NF1 gene product, as shown by several criteria, including partial proteolysis. Subcellular fractionation revealed that while GAP is predominantly cytoplasmic, all of the NF1 was recovered in a pellet (100,000 x g) fraction. NF1 was present in a large molecular mass complex in fibroblast and Schwannoma cell lines and appears to associate with a very large (400-500 kDa) protein in both cell types. The relevance of these findings to cellular regulation of p21ras is discussed.